Trends and outcomes of percutaneous coronary intervention during the COVID-19 pandemic in Michigan - Azzalini, Lorenzo; Seth, Milan; Sukul, Devraj; Valle, Javier A.; Daher, Edouard; Wanamaker, Brett; Tucciarone, Michael T.; Zaitoun, Anwar; Madder, Ryan D.; Gurm, Hitinder S. (PLOS ONE, 2022)
Background The COVID-19 pandemic has severely impacted healthcare delivery and patient outcomes globally. Aims We aimed to evaluate the influence of the COVID-19 pandemic on the temporal trends and outcomes of patients undergoing percutaneous coronary intervention (PCI) in Michigan. Methods We compared all patients undergoing PCI in the BMC2 Registry between March and December 2020 (“pandemic cohort”) with those undergoing PCI between March and December 2019 (“pre-pandemic cohort”). A risk-adjusted analysis of in-hospital outcomes was performed between the pre-pandemic and pandemic cohort. A subgroup analysis was performed comparing COVID-19 positive vs. negative patients during the pandemic. Results There was a 15.2% reduction in overall PCI volume from the pre-pandemic (n = 25,737) to the pandemic cohort (n = 21,822), which was more pronounced for stable angina and non-ST-elevation acute coronary syndromes (ACS) presentations, and between February and May 2020. Patients in the two cohorts had similar clinical and procedural characteristics. Monthly mortality rates for primary PCI were generally higher in the pandemic period. There were no significant system delays in care between the cohorts. Risk-adjusted mortality was higher in the pandemic cohort (aOR 1.26, 95% CI 1.07–1.47, p = 0.005), a finding that was only partially explained by worse outcomes in COVID-19 patients and was more pronounced in subjects with ACS. During the pandemic, COVID-19 positive patients suffered higher risk-adjusted mortality (aOR 5.69, 95% CI 2.54–12.74, p<0.001) compared with COVID negative patients. Conclusions During the COVID-19 pandemic, we observed a reduction in PCI volumes and higher risk-adjusted mortality. COVID-19 positive patients experienced significantly worse outcomes.